Simultaneous vibration reduction and energy harvesting of a nonlinear oscillator using a nonlinear electromagnetic vibration absorber-inerter. (July 2021) - Kakou, Paul; Barry, Oumar
Highlights: A nonlinear vibration control and energy harvester namely NERS-TMDI is proposed. The numerical results are verified using the harmonic balance method. NERS-TMDIs perform better than existing approaches on nonlinear oscillators. Grounding the electromagnetic device improves the performance of the NERS-TMDI. Abstract: Recently, considerable attention has been given to electromagnetic resonant shunt tuned mass damper-inerters (ERS-TMDI) for simultaneous vibration mitigation and energy harvesting. The application of this design is already well-established for linear structures, however, it is not extensively explored for nonlinear structures. This work, for the first time, aims to achieve both vibration mitigation and energy harvesting for nonlinear oscillating structures using a single device. For this, a novel nonlinear electromagnetic resonant shunt tuned mass damper-inerter (NERS-TMDI) is proposed with two different configurations. The proposed NERS-TMDI is coupled to a nonlinear oscillator via linear and nonlinear springs. For the first configuration, the electromagnetic and the inerter devices are grounded on one side and connected to the nonlinear vibration absorber on the other side. In the second configuration, the electromagnetic device is placed between the nonlinear vibration absorber and the primary structure. The nonlinear governing equations of motion are solved analytically using the method of harmonic balance in conjunction with the fixed arc-length continuation method. The analytical approach is validated using numerical simulations. A detailed parametric analysis for both configurations is conducted to identify the key design parameters that render the best performance of the NERS-TMDI. The results show that the proposed NERS-TMDI configurations perform better than the existing approaches, including the nonlinear tuned mass damper (NTMD), and the ERS-TMDI, in terms of vibration control. The results also show that the first configuration of NERS-TMDI always performs better for simultaneous vibration mitigation and energy harvesting than the second configuration of NERS-TMDI. This implies that grounding the electromagnetic transducer extends the range of effectiveness of the NERS-TMDI. Further, a sensitivity analysis on the optimal Configuration-1 showed that the NERS-TMDI is robust to variations in nonlinear stiffness, but its performance degrades for variations in inertance, resistance, inductance, and capacitance. Additionally, a parametric study demonstrates that higher values of nonlinear stiffness, inertance, and resistance, and lower values of inductance and capacitance render an optimal design of the Configuration-1 of the NERS-TMDI for energy harvesting. The findings are very promising and open a horizon of future opportunities to optimize the design of the NERS-TMDI for superior performance.